Training IoT Development for Enhancing Search and Rescue Tracking and Educational Tools - Maulindar, Joni; Andrianto, Albertus Ari; Nandita Sekar Sukma Dewi (Asian Journal of Community Services, 2024)
The Internet of Things (IoT) Development Training at Universidade Oriental Timor Lorosa’e aims to address challenges in tracking search and rescue teams and enhance educational tools. This training is designed to provide an in-depth understanding of IoT technology and its applications in operational and educational contexts. The methods used include theoretical sessions, hands-on practice, and project evaluation. The evaluation results show a significant increase in participants' knowledge levels: understanding of IoT concepts increased from 40% to 85%, knowledge of IoT applications rose from 35% to 80%, the ability to use IoT devices improved from 30% to 75%, and skills in developing IoT systems advanced from 25% to 70%. The success of this training reflects the positive impact of IoT technology in enhancing participants' skills, potentially bringing long-term benefits to both fields discussed at Universidade Oriental Timor Lorosa’e.